Is it beneficial to perform surgical resection in elderly patients more than 80 years old with advanced gastric cancer?. (3rd October 2017) - Choo, Jin Woo; Ju, Yeonmi; Lim, Hyun; Youn, Sung Hee; Soh, Jae Seung; Park, Ji Won; Kang, Ho Suk; Kim, Sung Eun; Moon, Sung Hoon; Kim, Jong Hyeok; Park, Choong Kee; Ha, Hong Il; et al.
Abstract: Objectives: With the aging population, the number of elderly patients diagnosed with gastric cancer is increasing. However, determining treatment strategies for elderly patients with gastric cancer is controversial. The aim of this study is to evaluate the usefulness of surgical treatment on elderly patients aged ≥80 years with advanced gastric cancer. Methods: A total of 147 elderly patients who were diagnosed with advanced gastric cancer from August 2001 to December 2015 were retrospectively analyzed. We compared the clinicopathological features and prognoses of 94 elderly patients (80–85 years) and 53 extreme-elderly patients (≥86 years) according to treatment modalities. Results: In the elderly group, the 3-year overall survival (OS) rates of the surgical resection group and supportive care group were 42.1% and 4.0%, respectively ( p  < .001). In the extreme-elderly group, the 3-year OS rates of the surgical resection group and supportive care group were 36.4% and 8.0%, respectively ( p  = .028). The post-operative mortality rate of the elderly group and extreme-elderly group was 5.6% and 9.1%, respectively. In the analysis of risk factors associated with survival, surgical resection was a significantly good prognostic factor in the elderly group (hazard ratio [HR] = 0.277; p  = .003) compared with supportive care. In the extreme-elderly group, surgical resection was associated with good prognosis but did not reach statistical significance (HR = 0.491; p  = .099). Conclusions: These results suggest that elderly patients aged 80–85 years with advanced gastric cancer could expect a better prognosis with surgical resection. However, extreme-elderly patients aged ≥86 years should consider the risks and benefits of surgical treatment.